PERCEPÇÃO DE FATORES E SITUAÇÕES DE RISCO EM MOTORISTAS INFRATORES - Beil, Sibele Luzia (2007)
This application had the objective to verify the perception of situations occurred in traffic accident, caused by transgressions drivers; uprising data social demographic, facts of risk also them protection and invulnerability of transgressions drivers. The collection of data, was realize trough the application of invulnerability social perception, demographic questionnaire, it aimed at characterize the conductor by the half structuralized interview with objective to know the actions of conductor at the flywheels. The sample basis was realizing by accessibility. The criteria include the qualified driver s with more than twenty points in they re driver s license. This application had 427 people, being 325 man and 102 women. The transgressions more committed were the serious for the both people stuff qualified between 6 and 15 years. In relation of invulnerability scale, the positive selfperception was superior than the sense of protection and creed at fellow invulnerability. The interviewees has in average 38 points in they re dossier, but consider they re self: cautiously, carefully and worriedly with others, and looking for to attempt the laws. The risk was associate with the idea of danger, caused damage to the other peoples or compromise the public security. The situations of risk were associates at the excessive volume of vehicles, high speed, not attendance at traffic laws, bad conservation of vehicles and absence of traffic signalizations. The perception of risks has much seen with singularity individual, in front of something with estimated the right probability. The evidence with the traffic transgressions occurred has to do with the social contest. To investigate about the possible psychologist variants in that contest also them function with big largeness. The application realized in Brazil at the traffic psychology, able on more step in the direction of comprehension of complex relation involving the human, the traffic and the environment.(AU)